First Case Report of Deferiprone-Induced Anaphylactic Reaction - Naharuthai Bumrungratanayos; Songphol Tungjitviboonkun (My University, 2024)
A 56-year-old Thai male, known for allergies to penicillin, sulfa, and lincosamide, presented with hyperferritinemia. Upon initiating deferiprone therapy, the patient experienced recurrent episodes of dyspnea, culminating in anaphylactic shock. Treatment included subcutaneous epinephrine, intravenous chlorpheniramine, and hydrocortisone, which led to symptom resolution. This case constitutes the first case report of deferiprone-associated anaphylactic reactions.
Keywords: Deferiprone; Anaphylactic shock; Anaphylactic reactions; Drug-Induced Adverse Reactions